REMAJA CERDAS FINANSIAL: KESADARAN MENABUNG DAN ALOKASI 50/30/20 DALAM MEWUJUDKAN STABILITAS KEUANGAN MASA DEPAN - Al Panndi Dyanata; Azid Bustomi; Meisya Kamila Saraswati; Rifki Zulfauji (Jurnal Abdi Citra, 2026)
The Student Community Service titled "Smart Financial Teens: Saving Awareness and 50/30/20 Allocation in Achieving Future Financial Stability" was held by Accounting students at Universitas Pamulang at Panti Asuhan Adinda. This program aims to raise saving awareness and understanding of the 50/30/20 budgeting method among orphanage teenagers to manage finances wisely and build future financial stability. Methods included material delivery, interactive quizzes, and piggy bank distribution for practice. Results showed increased knowledge and readiness to adopt positive financial habits. This activity contributed to developing responsible financial behavior among vulnerable youth.